2019
DOI: 10.1111/modl.12586
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Distribution of Practice Effects for the Learning of Foreign Language Verb Morphology in the Young Learner Classroom

Abstract: Within limited‐input language classrooms, understanding the effect of distribution of practice (spacing between practice) on learning is critical, yet evidence is conflicting and of limited relevance for young learners. For second language (L2) grammar learning, some studies reveal advantages for spacing of 7 days or more, but others for shorter spacing. Further, little is known about the role of cognitive individual differences (e.g., language analytic ability; LAA) in mediating practice distribution effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 64 publications
8
53
1
Order By: Relevance
“…These limitations notwithstanding, our findings provide a number of directions for future research on differences between instructional components and their impact on L2 learning. For example, it is unclear whether systematic production practice (L2 vs. L2+L1), instead of comprehension practice, would lead to the same learning gains, or the extent to which altering the amount or spacing of practice would affect the findings (see Kasprowicz & Marsden, ; Suzuki, ). As previously noted, learners completed extensive L2 practice, but very little L1 practice in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations notwithstanding, our findings provide a number of directions for future research on differences between instructional components and their impact on L2 learning. For example, it is unclear whether systematic production practice (L2 vs. L2+L1), instead of comprehension practice, would lead to the same learning gains, or the extent to which altering the amount or spacing of practice would affect the findings (see Kasprowicz & Marsden, ; Suzuki, ). As previously noted, learners completed extensive L2 practice, but very little L1 practice in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Kasprowicz, Marsden, and Stephton () contextualize their research in foreign language instruction among primary school students who spent only a few hours on foreign language learning each week. The study focused on young learners of French (aged 8–11) whose first language is English.…”
Section: In This Special Issuementioning
confidence: 99%
“…Kasprowicz, Marsden, and Stephton's () study is set in the context of foreign language instruction for young children in schools, a population which, as the authors point out, is greatly ‘under‐researched’ in SLA studies, particularly studies that take a psycholinguistic approach to language learning. And yet, the question of how aspects of practice affect learning outcomes with this population is especially needed in light of the widely held belief that young learners are somehow ‘better’ learners, whose learning proceeds with little effort.…”
Section: In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Strong and Boers () reported that the retrieval condition led to more successful performance during learning (88%) than the trial‐and‐error condition (18%). Kasprowicz, Marsden, and Sephton () did not find a statistically significant difference between long and short spacing in learning phase performance (7‐day: 79.6%, 3.5‐day: 82.5%). However, a number of studies demonstrate that long spacing induces more errors during the learning phase than short spacing (e.g., Brown, Roediger, & McDaniel, ; Nakata & Suzuki, ; Nakata & Webb, ; Pashler, Zarow, & Triplett, ; Toppino & Gerbier, ).…”
Section: Expounding On Learning Processes During L2 Practicementioning
confidence: 91%